Social determinants of health influencing diabetes self-care behaviors among immigrants: a scoping review - Rie Kudoh; Taiga Shibayama (Frontiers in Clinical Diabetes and Healthcare, 2026)
Background As globalization accelerates, immigrants face diabetes management challenges that are a public health concern. Although Social Determinants of Health (SDOH) are recognized as key drivers of health status and access to care, their role in diabetes self-care behaviors among immigrants remains unclear. Objectives This scoping review aimed to identify and map SDOH influencing diabetes self-care behaviors among immigrants in host countries. Methods PubMed and Web of Science were searched for peer-reviewed empirical studies (qualitative, quantitative, or mixed-methods) published in English between 2020 and 2024, following PRISMA-ScR framework, using terms related to immigrants, diabetes, self-care, and SDOH. Results Twenty-five studies met inclusion criteria, predominantly from the North America and Caribbean region (n = 17), with no studies identified from South-East Asia or Africa. All six SDOH domains were associated with at least one of five self-care behaviors. Community and Social Context was the most pervasive domain, influencing all behaviors. Economic Stability, Health and Healthcare System, and Education Access and Quality were associated with multiple behaviors, with financial constraints and language barriers. Food Environment and Neighborhood and Physical Environment, as environmental factors, were more selectively associated; Food Environment with diet, and Neighborhood and Physical Environment with physical activity and medical visits. Conclusion Diabetes self-care among immigrants is shaped by a complex interplay of structural and environmental factors, highlighting the need for culturally tailored, multilevel interventions to reduce self-care disparities. The absence of evidence from South-East Asia and Africa represents a critical gap, and future research in these underrepresented regions is warranted.